Pengembangan Bahan Ajar Matematika Berbasis Problem Based Learning Pada Siswa Sekolah Dasar - Lestari, Fida; Egok, Asep Sukenda; Febriandi, Riduan (Universitas Pahlawan Tuanku Tambusai, 2021)
This study aims to develop teaching materials based on Mathematics Based Problem-Based Learning in fifth grade students of SD 37 Lubuklinggau in accordance with the 2013 curriculum and to produce valid and practical teaching materials for use in learning. This research is a development study with a development model adapted from the Four-D model. Based on the results of the analysis Based on the experts, namely: linguists, material experts, and media experts determine statistical teaching materials based on problem-based learning criteria meet the criteria with an average score of 0.76. Based on the analysis of teacher and student worksheets consisting of 9 people obtained from problem-based learning based statistical teaching materials meet the requirements with an average score of 95%, so that learning materials can be improved based on statistical problems Problem Based Learning requires valid, practical criteria and can be used in learning. Keywords: Development, Mathematic Teaching Materials, Problem Based Learning